Bio-inspiration unveiled: Dissecting nature’s designs through the lens of the female locust’s oviposition mechanism - Amir Ayali; Shai Sonnenreich; Bat El Pinchasik (iScience)
Summary: Investigating nature’s ingenious designs and systems has become a cornerstone of innovation, influencing fields from robotics, biomechanics, and physics to material sciences. Two key questions, however, regarding bio-inspired innovation are those of how and where does one find bio-inspiration? The perspective presented here is aimed at providing insights into the evolving landscape of bio-inspiration discovery. We present the unique case of the female locust’s oviposition as a valuable example for researchers and engineers seeking to pursue multifaceted research, encompassing diverse aspects of biological and bio-inspired systems. The female locust lays her eggs underground to protect them and provide them with optimal conditions for survival and hatching. To this end, she uses a dedicated apparatus comprising two pairs of special digging valves to propagate underground, while remarkably extending her abdomen by 2- to 3-fold its original length. The unique digging mechanism, the subterranean steering ability, and the extreme elongation of the abdomen, including the reversible extension of the abdominal central nervous system, all spark a variety of questions regarding materials, morphology, mechanisms, and their interactions in this complex biological system. We present the cross-discipline efforts to elucidate these fascinating questions, and provide future directions for developing bio-inspired technological innovations based on this remarkable biological system.